Ether : The Nothing That Connects Everything - Milutis, Joe (Book collections on Project MUSE., 2006)
In Ether, the histories of the unseen merge with discussions of the technology of electromagnetism. Navigating more than three hundred years of the ether's cultural and artistic history, Joe Milutis reveals its continuous reinvention and tangible impact without ever losing sight of its ephemeral, elusive nature. The true meaning of ether, Milutis suggests, may be that it can never be fully grasped.